The impact of SA Rand devaluation on the livelihoods of recipients of Diaspora Remittances in Chiredzi urban. - Magombedze, Tafadzwa G. (Midlands State University, 2017)
The main purpose of this research was to explore the effects of SA rand devaluation on the welfare of families in Chiredzi urban district that depend on remittances send to them by those in SA diaspora. It is clear that diaspora remittances have been a source of livelihood for a lot of Zimbabweans since the decline of the local industry have resulted in people looking for other opportunities elsewhere outside the country. In Chiredzi urban there is a lot of informal activities making the town vulnerable to high levels of migration during tough times. The high dependence on diaspora remittances was mainly embraced from the early 2000 when the Zimbabwean economy started experiencing its toughest challenges, then remittances came as a short term survival strategy and in most cases it became a long term livelihood. The research therefore seeks to find the problems being experienced as a result of rand devaluation and overdependence on this rand. The researcher then used mixed research approach were both qualitative as well as quantitative research methodologies were employed so as to gain both analysis of experiences and econometrics surrounding rand devaluation. It was a longitudinal research design were data of past and present events was collected from selected families and key informant agencies. Particular attention was however given to the families’ experiences in terms of their livelihoods including income, assets acquired, food security, children’s welfare, health care and general standard of living. To assess the pattern of money transfers into Chiredzi as a district international money transfer agents were also approached for data collection. The research reviewed that rand devaluation had a devastating negative impact to the livelihoods of those who depend on it mainly affecting the household income in USD due to the unfavourable volatile exchange rates in the recent past. The study also looked a little bit on how these families managed to survive such an external blow brought by the devaluing rand.